Lipid Profile Changes in Patients With Chronic Inflammatory Arthritis Treated With Biologic Agents and Tofacitinib in Randomized Clinical Trials: A Systematic Review and Meta‐Analysis. Issue 1 (January 2015) - Souto, Alejandro; Salgado, Eva; Maneiro, José Ramón; Mera, Antonio; Carmona, Loreto; Gómez‐Reino, Juan J.
<x xml:space="preserve">Abstract</x> Objective To analyze lipid changes in patients with rheumatoid arthritis (RA) and patients with spondyloarthritis (SpA) treated with biologic agents or tofacitinib in randomized clinical trials (RCTs). Methods A systematic literature search was performed, using the Medline, Embase, Cochrane Library, and Web of Knowledge databases. Meta‐analyses were performed using random‐effects models to assess changes in the percentage of patients with abnormal lipid values or in the mean percentage of increase in the cholesterol and triglycerides levels. Results Twenty‐five of 4, 527 identified articles met the inclusion criteria. Compared with RA patients treated with placebo, those treated with tocilizumab were more likely to have hypercholesterolemia (odds ratio [OR] 4.64; 95% confidence interval [95% CI] 2.71, 7.95 [P < 0.001]), increased levels of high‐density lipoprotein (HDL) cholesterol (OR 2.25; 95% CI 1.14, 4.44 [P = 0.020]), and increased levels of low‐density lipoprotein (LDL) cholesterol (OR 4.80; 95% CI 3.27, 7.05 [P < 0.001]); this was not observed in patients treated with tumor necrosis factor (TNF) antagonists (OR 1.54; 95% CI 0.90, 2.66 [P = 0.119]) or tofacitinib (OR 3.4; 95% CI 0.62, 18.55 [P = 0.158]). Among patients receiving tofacitinib 5 mg twice daily, the mean percentage of increases in the HDL cholesterol level (weighted mean difference [WMD] 13.00 mg/dl; 95% CI 12.08, 13.93 [P < 0.001]) and the LDL cholesterol level (WMD 11.20 mg/dl; 95% CI 10.08, 12.32 [P < 0.001]) were higher than those in the comparator groups. Among patients treated with tofacitinib 10 mg twice daily, the mean percentage of increases in the HDL cholesterol level (WMD 15.21 mg/dl; 95% CI 13.28, 17.14 [P < 0.001]) and the LDL cholesterol level (WMD 15.42 mg/dl; 95% CI 11.77, 19.06 [P < 0.001]) were also higher than those in the comparator groups. No data were available for RA treated with other biologic agents or for SpA. Conclusion In patients with RA treated with tocilizumab or tofacitinib but not with TNF antagonists, moderate changes in lipids are observed. Whether these changes pertain to the control of inflammation or to the mechanism of action of the biologic agents or tofacitinib remains undetermined.